Modelling and practical studying of heat recovery steam generator (HRSG) drum dynamics and approach point effect on control valves - Ahmed Shams El-din Ahmed; Mostafa A. Elhosseini; Hesham Arafat Ali (Ain Shams Engineering Journal, 2018)
In this paper, we present a simple procedure to build a model of a heat recovery steam generator (HRSG) evaporator and drum within the environment of MATLAB/Simulink. The HRSG is part of combined cycle power plant that is located at Talkha power station (130 km north of Cairo, capital of Egypt). The model captures the response of water and steam inside HRSG evaporator and drum like drum level, pressure, steam quality and others during different conditions. We discuss some practical concepts in HRSG design, and the importance of HRSG approach point value to drum level stability and control. We also discuss how HRSG approach point can have destroying effect on level control valves of the drum and increase the maintenance cost of the combined cycle power plant. Keywords: Heat recovery steam generator, Evaporator, Model, Drum, Combined cycle